Noun Phrase In Minang Language - Akmal Akmal; Jamaluddin Nasution (Magister Pendidikan Nonformal Pascasarjana Universitas Negeri Gorontalo, 2021)
Phrase structure rules express the basic structural facts of the language in the form of “phrase markers”. This study discussed about the noun phrase in Minangkabau Language. The aim of this study is to find out the noun phrases of Minangkabau Language and how the noun phrases are used in the language. The used method is qualitative research design by interviewing the native speakers of Minangkabau by using the depth interview. the participants are the people who lived in Sukaramai Districts. They were born in Pariaman Districts and they are educated people who understand about the phrase structure.The researcher described the finding data more details. In this study, there are six noun phrase forms in Minangkabau Language and there is one unique form. The noun phrases are implicated in the daily activity of society. In fact, there was a unique noun phrase in Minang Language namely: Noun Phrase (NP) is N1 + sa + N2.